2020
DOI: 10.34172/jcvtr.2020.30
|View full text |Cite
|
Sign up to set email alerts
|

Presence of ear lobe crease may predict intermediate and high-risk patients with acute non-ST elevation acute coronary syndrome

Abstract: Introduction: Ear lobe crease (ELC) was first described in 1973 as a physical examination finding indicating significant coronary artery disease (CAD). Several studies have been carried out in relation to this finding, and it has been shown that it is a marker of intima-media thickness, carotid artery disease, and CAD. We aimed to investigate the relationship between earlobe crease, which is a simple physical examination finding, and GRACE score as a risk estimation index in acute coronary syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…An association between ELC and coronary atherosclerosis has been identified in clinical [1][2][3][11][12][13] and necropsy [14][15][16] studies. A previous meta-analysis [12] has revealed a potential association between ELC and the presence of coronary artery disease, with an odds ratio of 3.3.…”
Section: Earlobe Creases and The Severity Of Coronary Atherosclerosismentioning
confidence: 99%
“…An association between ELC and coronary atherosclerosis has been identified in clinical [1][2][3][11][12][13] and necropsy [14][15][16] studies. A previous meta-analysis [12] has revealed a potential association between ELC and the presence of coronary artery disease, with an odds ratio of 3.3.…”
Section: Earlobe Creases and The Severity Of Coronary Atherosclerosismentioning
confidence: 99%
“…50% stenosis on CCTA and showed that ELC was independently associated with MVD even after adjusting for the age, sex, symptoms, and other conventional coronary risk factors (odds ratio =1.9, P=0.010) (3). Kahyaoglu et al performed a retrospective study of 360 patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) and found that patients with ELC had a significantly higher Gensini score than those without ELC (32 vs. 16, P<0.001) (9).…”
Section: Discussionmentioning
confidence: 99%
“…DELC has been identified in the medical literature as a surrogate marker for identifying high-risk patients with occult atherosclerosis [3][4][5]. It has been found to be more prevalent in males, and a statistically significant positive association was observed between DELC and conditions such as diabetes mellitus, hypertension, myocardial infarction and coronary artery disease in both sexes [6].…”
Section: Introductionmentioning
confidence: 99%